Characteristic of calcined diatomaceous earth from Aceh Besar District - Indonesia as cementitious binder. Issue 1 (September 2020) - Hasan, M; Saidi, T; Muyasir, A; Alkhaly, Y R; Muslimsyah, M
Abstract: Diatomaceous earth is a naturally occurring, soft, siliceous sedimentary rock, which is easily crumbled into a fine powder. In this paper, the characteristic of calcined diatomaceous earth from Aceh Besar District – Indonesia as a cementitious binder is studied. The chunk of diatomaceous earth was burned in the brick burning furnace for 4 days, then ground so that it becomes a powder. The powder was sieved to form the binder having the particle sizes less than 250 μm. The binder then calcined at the temperature of 600°C for 5 hours in a laboratory furnace. The density, specific gravity, absorption, particle size analyzer, X-ray diffraction, X-ray fluorescence, and scanning electron microscopy tests were therefore performed. The test results show that the density, saturated surface dry specific gravity, and absorption of calcined diatomaceous earth binder are 767 kg/m 3, 2.000, and 6.535 %, respectively. The particle sizes range from 0, 107 μm to 231 μm. The main minerals of the particle are graphite, quartz, and lead-silver thallium antimony sulphide. The main chemical compositions of calcined diatomaceous earth are SiO2, 56.00 %; Fe2 O3, 26.40 %; ZrO2, 7.20 %; and Al2 O3, 6.50 %.